Analisis Potensi Interaksi Obat Pada Pasien Diabetes Melitus Tipe II Dengan Kompetensi Hipertensi Di RS Kota Pekanbaru - Rahmawati, Ayu; Lubis, Nursyafni; Nawwar Irfan; Muhammad Arif; Putri Afriani (LPPM, Universitas Muhammadiyah Riau, 2025)
Patients with type 2 Diabetes Mellitus accompanied by hypertension commonly receive multiple medications, increasing the risk of polypharmacy and potential drug interactions. This study aimed to analyze the relationship between the number of drugs used and the occurrence of potential drug interactions among patients with type 2 Diabetes Mellitus and hypertension at Hospital Ini Pekanbaru City. This study employed a non-experimental observational design with retrospective data collection. Samples were selected using purposive sampling, and data were analyzed using IBM SPSS Statistics version 27. A total of 98 medical records met the inclusion criteria. The results showed that 57 patients experienced potential drug interactions, with a total of 67 interaction events. All identified interactions were classified as moderate in severity (100%). Based on the interaction mechanisms, pharmacodynamic interactions were predominant, accounting for 64 events (95.52%), while pharmacokinetic interactions accounted for 3 events (4.48%). Statistical analysis demonstrated a significant association between the number of drugs prescribed and the occurrence of potential drug interactions (p = 0.001). Close monitoring of potential drug interactions is essential to ensure the effectiveness and safety of therapy, particularly in patients undergoing polypharmacy.